Analisis Kepuasan Pengguna Sistem Informasi Akademik Menggunakan Metode End-User Computing Satisfaction - Reza Saputra; M Rudi Sanjaya (STMIK Budi Darma, 2023)
Academic Information System (SIMAK) is an academic information service provided by Sriwijaya University and is basically a mechanism used to manage academic and statistical information in it. The purpose of this research is to measure the level of user satisfaction in using the academic information system website, the method used is the EUCS (End-User Computing Satisfaction) method which is assessed from the aspects of content, format, accuracy, user convenience and timeliness. Data collection in this study used a questionnaire distributed to SIMAK users. The validity and reliability test results of the questionnaire questions are valid and reliable. In calculating the data from the questionnaire results using the average satisfaction formula and the Kaplan and Norton categories. The results of this study are to improve the quality of the features of the academic information system website fasilkom unsri, the number of research respondents as many as 313 people showed from the five aspects namely Accuracy, Content, Format, Timeliness, User Convenience are in the satisfied category and become suggestions to developers to maintain and improve the SIMAK website